2021
DOI: 10.3892/ol.2021.13059
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA NUTM2A‑AS1 inhibits lung adenocarcinoma cell viability by regulating the miR‑590‑5p/METTL3 axis

Abstract: Lung adenocarcinoma (LUAD) is the leading cause of cancer-related mortality worldwide. Long non-coding RNA (lncRNA) NUT family member 2A antisense RNA 1 (NUTM2A-AS1) is dysregulated in LUAD; however, its role in this disease remains unclear. The present study aimed to identify the underlying molecular mechanism of the effect of lncRNA NUTM2A-AS1 in LUAD by exploring whether lncRNA NUTM2A-AS1 could affect LUAD cell proliferation and apoptosis through the microRNA (miR)-590-5p/methyltransferase 3, N6-adenosine-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Approximately 60% of the NUTM2A-AS1::RP11-203L2.4 containing tumor cells were solely identified by long read evidence, another 20% by short reads only, and the remaining 20% by both short and long reads ( Figure 5b ). Interestingly, fusion gene partner NUTM2A-AS1 has recently been identified as an oncogene with roles in multiple cancer types (Wang et al 2020; Wang et al 2021; Long et al 2023). The long fusion reads appear to be largely full-length and yield evidence for eight different fusion splicing isoforms, mostly involving skipping of alternative exons and one isoform involving an alternative terminal exon ( Figure 5c ).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 60% of the NUTM2A-AS1::RP11-203L2.4 containing tumor cells were solely identified by long read evidence, another 20% by short reads only, and the remaining 20% by both short and long reads ( Figure 5b ). Interestingly, fusion gene partner NUTM2A-AS1 has recently been identified as an oncogene with roles in multiple cancer types (Wang et al 2020; Wang et al 2021; Long et al 2023). The long fusion reads appear to be largely full-length and yield evidence for eight different fusion splicing isoforms, mostly involving skipping of alternative exons and one isoform involving an alternative terminal exon ( Figure 5c ).…”
Section: Resultsmentioning
confidence: 99%
“…In a hypoxic tumour microenvironment, it eventually protects gastric cancer cells from ferroptosis [ 56 ]. Knockdown of lncRNA NUTM2A-AS1 suppresses lung adenocarcinoma cell viability and induces apoptosis through the miR-590-5p/METTL3 axis [ 57 ]. Overall, numerous experimental findings indicate that lncRNAs regulated by RNA methylation play a critical role in bringing about, developing, and metastasizing cancerous tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lncRNA can also affect the function of genes related to RNA methylation modification. For example, knockdown of Nutm2a-as1 can regulate Mettl3 to inhibit lung cancer progression ( Wang J. et al, 2021 ). Song et al used a systems approach to integrate gene expression and patient survival data with protein interaction networks in discrete windows of tumor proliferative biology and demonstrated that, in combination, these networks may form the basis of highly accurate prognostic classification models, with potential clinical utility for guiding therapeutic options for patients ( Song et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%